Enhancing nonspecific immune response of grouper "Epinophelus coioides" using levamisole as immunostimulant. - Mendoza, Sharon Ann G. Pedrajas (UP in the Visayas, 2004)
The use of levamisole as an alternative approach to disease prevention and control has been resorted to in aquaculture. Its immunomodulatory effect in several fish species is well documented but its effect on grouper, Epinephelus coioides requires further investigation. To determine its immunomodulatory effect on grouper, juveniles were injected and fed with levamisole. Intraperitoneal injection (IP) at 0 (control), 0.5, 5, 10, 20 and 50 mg levamisole/kg body weight was administered. Grouper were also fed diets containing 0 (control), 125, 250 and 500 mg levamisole/kg supplemental dry diet for 10 days. Hematocrit levels, total and differential leucocyte counts and bactericidal activity were examined 7 days post IP. Three, 5 and 7 weeks after last administration of supplemented feeds, growth and bactericidal activity were checked. A significant (P<0.05) increase in the total leucocyte count was noted in the injection-treated fish. Granulocyte (19.39%) and monocyte (27.38%) percentages increased while lymphocyte (53.40%) population decreased in the differential leucocyte count. However, hemtocrit levels were not affected by levimasole. Bactericidal activity against Vibrio anguillarum increased in treated (injected and supplemented) fish. A significant (P<0.05) increase in weight of juveniles was observed 10 days after last feeding with supplemented diet. Groupers injected with 0.5 mg levamisole/kg body weight and those supplemented with 125 mg levamisole/kg dry diet exhibited the most significant (P<0.05) changes in parameters tested indicating immunostimulation. Growth (weight gain) and bactericidal activity peaked 5 weeks post administration of levamisole in the feeding experiment. Results of the present study strongly suggest that levamisole can enhance nonspecific defenses in grouper and opens the possibility of using immunostimulants in grouper culture.